Kandungan Antioksi dan Asam Askorbat pada Jus Buah-Buahan Tropis - Febrianti, Novi; Yunianto, Irfan; Dhaniaputri, Risanti (JURNAL BIOEDUKATIKA, 2015)
Tropical fruits are rich in nutrients and phytochemicals that benefit our health. As source of antioxidant, regular consumption of fruits will be useful in avoiding many degenerative diseases particularly caused by free radicals. The good effects of antioxidants vary from repairing tissue damages in respiratory system, excretory system as well as reproductive system. Ascorbic acid is one potent antioxidant that has been recorded for history. Known as Vitamin C, its concentration in fruits has been a primary consideration for people to choose what kind of fruit they are going to consume. This experimentâs result exhibited different levels of ascorbic acid in some topical fruits. Average concentration of ascorbic acid from the highest to lowest was obtained in orange, guava, apple, papaya, tamarind and mango with their contents of 96,8; 49,86; 49,57; 48,4 and 41,06 mg/100g, respectively. This result would be a baseline in setting the best fruit combination to obtain maximum effects of antioxidant.